(untitled) (Interdisciplinary Studies Journal, 2025)
This work aims to contribute to reflections on the importance of the Marxist method in cultural analyses as well, outlining a brief history of the emergence of the postmodern proposal as an alternative for the same purpose, based on the argument of the "traditional Marxism" being too rigid. In dialogue with authors such as Maria Elisa Cevasco and Marcelo Badaró Mattos, we seek to demonstrate some contradictions of materialist cultural criticism, as well as the proximities and differences between concepts such as relativism—in the postmodern perspective—and historicism—within the dialectical historical materialism framework. Finally, we conclude that the polarization of these two methodological alternatives also involves more complex political disputes, often reduced to intellectual simplifications with a seemingly clear purpose: to prevent radical social transformations.